2020
DOI: 10.1177/0972753120950069
|View full text |Cite
|
Sign up to set email alerts
|

What We Fail to See in Neuro-Genetic Diseases: A Bird’s Eye View from the Developing World

Abstract: Background: Progressive neurological genetic diseases are not rare. They cause psychosocial damages to its victims. This article focuses on common psychosocial issues faced by those from the developing world. Methods: A multicentre observational survey of 246 patients from teaching hospitals in Sri Lanka. Participants were clinically and genetically confirmed by neurologists and the Interdisciplinary Centre for Innovation in Biotechnology and Neuroscience (ICIBN) respectively from 2014 to 2018. Convenience sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It is notable that diagnostic delays persist in traditionally disadvantaged groups, such as patients from developing countries and with lower socioeconomic status, because access to subspecialty care and genetic testing is difficult for patients from developing countries [ 7 ], including Sri Lanka [ 6 ]. (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is notable that diagnostic delays persist in traditionally disadvantaged groups, such as patients from developing countries and with lower socioeconomic status, because access to subspecialty care and genetic testing is difficult for patients from developing countries [ 7 ], including Sri Lanka [ 6 ]. (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the average age of diagnosis for DMD remained over a decade as 5 years, it has been reported that the average age of diagnosis in Europe has decreased below the age of 3 years, reflecting the impact of enhanced access to molecular diagnostics and increased primary physician awareness [ 5 ]. In contrast, diagnostic delays in DMD persist with notable frequency within traditionally marginalized populations encompassing individuals hailing from developing nations and those of a lower socioeconomic stratum [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In step with the World Health Organization’s vision of “harnessing genomic knowledge and having it contribute to health equity, especially among developing nations”, the corresponding author of this article received a donation of equipment through the International Brain Research Organization- Asia Pacific Regional Committee (IBRO-APRC) from National Institute of Neurological Disorders and Stroke (NINDS), of the National Institute of Health (NIH) USA in setting up, the only free genetic testing service in the state sector for selected neurodegenerative and neuromuscular disorders in Sri Lanka, which currently provides free genetic testing reports ( Samaranayake et al, 2020 ), a DNA bank in a developing country, Sri Lanka, with samples from over 2000 patients with neurological disorders that include 623 samples from patients with rare diseases ( Wijekoon et al, 2020 ), A Brain Bank” - collections of 76 autopsy aging brain samples, performed with histopathological/immunohistochemical staining for neuropathology with genotyping for selective candidate genes, and Human resource development through international training scholarships for postgraduates and Neuroscience workshops conducted in Sri Lanka with funding from IBRO- APRC. Moreover Double Doctoral Opportunities with international universities are available and ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…the only free genetic testing service in the state sector for selected neurodegenerative and neuromuscular disorders in Sri Lanka, which currently provides free genetic testing reports ( Samaranayake et al, 2020 ),…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic delays in DMD remain frequent in traditionally disadvantaged groups, including patients from developing countries and those with a lower socioeconomic status [30,31]. Therefore, a potential approach could be suggested that involves identifying young male children with delayed developmental milestones and examining them for suggestive clinical symptoms of muscular dystrophy, followed by performing a CPK test.…”
Section: Discussionmentioning
confidence: 99%